STUDI EMPIRIS: DAMPAK ATMOSFER CAFE, NILAI PELANGGAN, DAN KUALITAS PELAYANAN PADA CITRA MEREK - Siswati, Endang (Unitri Press, 2025)
The purpose of this study is to investigate how customer value, service quality, and café atmosphere affect brand image. Eighty respondents who frequent Hono Cafe in Surabaya were selected at random to participate in the study. Following validity and reliability testing, the analysis was conducted using SPSS version 25.0. Multiple linear regression analysis, which included both t-tests and F-tests, was used to assess the hypotheses. The findings of the investigation show that while the café atmosphere has no discernible impact on brand image, consumer value and service quality do. However, when taken into account combined, the factors of customer value, service quality, and café atmosphere significantly affect company image.